2020
DOI: 10.1002/jso.26217
|View full text |Cite
|
Sign up to set email alerts
|

Cancer care in a Western Indian tertiary center during the pandemic: Surgeon's perspective

Abstract: Introduction: Following the nationwide lockdown in India, most hospitals shut down elective surgeries including cancer surgeries. We continued operating on patients with cancer at a tertiary referral center in Western India, which also served as a COVID care center. We also constructed a questionnaire, exclusive to surgeons, to determine the changes in treatment strategies as well as the response to the pandemic. Methods: The complications of all cases operated in the study period (March 22, 2020-June 30, 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(69 citation statements)
references
References 15 publications
(16 reference statements)
0
27
0
Order By: Relevance
“…Overall, 75% [c.i. 49%-95%, I 2 99%, number of studies: 10 ( 22 , 25 , 26 , 32 , 36 , 40 , 44 , 45 , 51 , 52 )] of studies reported delay of clinic visits. Stratification according to specialty seemed to show a lower proportion of visits delay in the surgery subgroup, but with only one study belonging to this subgroup.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 75% [c.i. 49%-95%, I 2 99%, number of studies: 10 ( 22 , 25 , 26 , 32 , 36 , 40 , 44 , 45 , 51 , 52 )] of studies reported delay of clinic visits. Stratification according to specialty seemed to show a lower proportion of visits delay in the surgery subgroup, but with only one study belonging to this subgroup.…”
Section: Resultsmentioning
confidence: 99%
“…PPE were routinely used by workers in 80% [c.i. 61%-94%, I 2 99%, number of studies: 16 ( 18 , 26 , 31 , 33 35 , 37 39 , 44 , 52 , 53 , 59 , 61 , 63 , 65 )] of cases. No moderator was alone able to explain the true heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the incidence of Grades II and III complications in the present scenario, as opposed to more Grades I and II complications in the previous year, maybe due to an attempt by the surgeons to intervene on the complications to facilitate early discharge. Interestingly, in the studies from Tata Memorial Hospital 13 and Ruby Hall Clinic, 19 there were no postoperative deaths.…”
Section: Discussionmentioning
confidence: 96%
“…Several tertiary level academic oncology centres from India have reported their experiences of cancer surgery during the pandemic 13‐19 . India's largest oncology centre was reported to have a decrease in operated cases by a third 20 .…”
Section: Discussionmentioning
confidence: 99%
“…A vital point worth highlighting is the mental burden on health care providers during the COVID‐19 pandemic. Authors have reported that surgeons and other providers face several types of burdens and challenges during the pandemic, including but not limited to the mental strain of not being able to operate, financial loss, social isolation, and burnout 48–50 . Unfortunately, these factors may have contributed to increasing suicide rates among health care providers 51 …”
Section: Discussionmentioning
confidence: 99%